CAUSE OF PREMATURE BIRTH AS A PROGNOSTIC FACTOR OF NEONATAL OUTCOME AND TYPE OF DELIVERY - Donić, Smiljana; Maglić, Rastko; Mandić, Vesna; Mandić, Milica; Kostić, Konstantin; Maglić, Dragana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Premature birth, occurring before the 37th gestational week, is commonly attributed to uterine contractions, premature rupture of the amniotic sac, or placental abruption. In 20% – 30% cases involving maternal or fetal complications, premature birth may be induced, often due to conditions such as preeclampsia, fetal growth retardation, or severe maternal heart disease.Aim: The study aims to determine whether the cause and time of preterm birth affect the neonatal outcome.Material and methods: This retrospective study analyzes patients prematurely born at the Obstetrics and Gynecology Clinic Narodni Front in 2020, the cause of their premature birth, as well as the status of the fetus after birth. In the study, we compared the neonatal outcome in spontaneously induced preterm birth.Results: Among all the births (n = 4,211), in the period between July and December 2020, there were 498 preterm births, i.e., 11.83%. Based on the data on the status of the premature infants' vital signs, the percentage of stillborn preterm infants was 8.9% while the percentage of live births was 91.1%. The Apgar score was the highest in neonates born by vaginal birth after the 34th week of gestation, with intact fetal membranes and spontaneous contractions. According to the study, 54.1% of preterm births ended in cesarean section due to gestational age younger than 28 weeks and with a predominantly pelvic presentation of the fetus.Conclusion: The high rate of premature births highlights a serious problem and suggests a continued rising trend, despite preventive efforts. Improved outcomes are seen in pregnancies reaching later gestational weeks, particularly after the 34th week of gestation, with intact fetal membranes and no signs of infection. Spontaneously born premature infants tend to have higher Apgar scores and better neonatal outcomes, as compared to induced births.
Keywords: preterm birth; premature infant; Apgar score